Tumor Stroma Area and Other Prognostic Factors in Pancreatic Ductal Adenocarcinoma Patients Submitted to Surgery - Amaral, Maria João (2023)
Pancreatic ductal adenocarcinoma (PDAC) has a dense stroma, responsible for up to 80% of its volume. The amount of stroma can be associated with prognosis, although there are discrepancies regarding its concrete impact. The aim of this work was to study prognostic factors for PDAC patients submitted to surgery, including the prognostic impact of the tumor stroma area (TSA). A retrospective study with PDAC patients submitted for surgical resection was conducted. The TSA was calculated using QuPath-0.2.3 software. Arterial hypertension, diabetes mellitus, and surgical complications Clavien-Dindo>IIIa are independent risk factors for mortality in PDAC patients submitted to surgery. Regarding TSA, using >1.9 × 1011 µ2 as cut-off value for all stages, patients seem to have longer overall survival (OS) (31 vs. 21 months, p = 0.495). For stage II, a TSA > 2 × 1011 µ2 was significantly associated with an R0 resection (p = 0.037). For stage III patients, a TSA > 1.9 × 1011 µ2 was significantly associated with a lower histological grade (p = 0.031), and a TSA > 2E + 11 µ2 was significantly associated with a preoperative AP ≥ 120 U/L (p = 0.009) and a lower preoperative AST (≤35 U/L) (p = 0.004). Patients with PDAC undergoing surgical resection with preoperative CA19.9 > 500 U/L and AST ≥ 100 U/L have an independent higher risk of recurrence. Tumor stroma could have a protective effect in these patients. A larger TSA is associated with an R0 resection in stage II patients and a lower histological grade in stage III patients, which may contribute to a longer OS.